The effect of initiation of renin–angiotensin system inhibitors on haemoglobin: A national cohort study. Issue 2 (5th July 2020) - Greenhall, George H.B.; Mansfield, Kathryn E.; Nitsch, Dorothea; Iwagami, Masao; Leyrat, Clémence; Johnston, Rosalynd; Smeeth, Liam; Tomlinson, Laurie A.
Abstract : Aims: To determine whether initiation of treatment with angiotensin converting enzyme inhibitors or angiotensin II receptor blockers (ACEI/ARBs) is associated with a subsequent reduction in haemoglobin in the general population. Methods: We undertook a national cohort study over a 13‐year period (2004–2016), using routine primary healthcare data from the UK Clinical Practice Research Datalink. We compared ACEI/ARB initiation with calcium channel blocker (CCB) initiation, to minimise confounding by indication. We included all first ACEI/ARB or CCB prescriptions in adults with at least 1 haemoglobin result in the 12 months before and 6 months after drug initiation. Our primary outcome was a ≥1 g/dL haemoglobin reduction in the 6 months after drug initiation. Results: We examined 146 610 drug initiation events in 136 655 patients. Haemoglobin fell by ≥1 g/dL after drug initiation in 19.5% (16 936/86 652) of ACEI/ARB initiators and 15.9% (9521/59 958) of CCB initiators. The adjusted odds ratio of a ≥1 g/dL haemoglobin reduction in ACEI/ARB initiators vs CCB initiators was 1.15 (95% confidence interval 1.12–1.19). Conclusion: ACEI/ARBs are associated with a modest increase in the risk of a haemoglobin reduction. For every 100 patients in our study that initiated a CCB, 16 experienced a ≥1 g/dL haemoglobin decline. If the effect is causal, 3 additional patients would have experienced this outcome if they had received an ACEI/ARB. This may have implications for drug choice and monitoring for many patients in primary care. Further research could identify patients at higher risk of this outcome, who may benefit from closer monitoring.